1994
DOI: 10.1017/s0022215100127896
|View full text |Cite
|
Sign up to set email alerts
|

Computed tomography of the temporal bone in tuberculous otitis media

Abstract: Nine cases of tuberculous otitis media were treated by us over the past 10 years. Six patients presenting with large tympanic membrane perforations were treated for suppurative otitis media at various ENT clinics. The remaining three patients presented without perforation. Intractable otorrhoea, aggravation of hearing loss, dizziness, and in one case facial palsy, resulted in eventual referral to us. Histological examination revealed a tuberculous granulation, confirming the diagnosis in most cases. CT in four… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 4 publications
(4 reference statements)
0
14
0
Order By: Relevance
“…[11] The middle ear mucosa may appear pale. [13] Abundant pale granulations appear to be characteristic of tuberculous otitis media. These granulations may be seen filling the middle ear during otoscopy and the mastoid during surgery.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[11] The middle ear mucosa may appear pale. [13] Abundant pale granulations appear to be characteristic of tuberculous otitis media. These granulations may be seen filling the middle ear during otoscopy and the mastoid during surgery.…”
Section: Discussionmentioning
confidence: 99%
“…These granulations may be seen filling the middle ear during otoscopy and the mastoid during surgery. [7,8,13,14,15,16,17] Involvement of the middle ear by tuberculosis has been described in all age groups, though more commonly in children. In the pre-antibiotic era, 2.8% of all the cases of chronic suppurative otitis media were tuberculous in nature and infants below one year of age comprised 50% of these.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have shown that CT is the best imaging modality available for the diagnosis of tuberculous mastoiditis; CT provides more information than do standard plain films and it is more accurate and useful than magnetic resonance imaging. [8,9] Histopathologic examination of the involved middle ear and mastoid mucosa will show three types of changes: miliary, granulomatous, and caseous. The miliary type is associated with superficial infection, the granulomatous type with superficial bony involvement, and the caseous type with massive necrosis and sequestration.…”
Section: Discussionmentioning
confidence: 99%
“…Mastoid X-rays in our patient showed well pneumatized mastoid with no evidence of any haziness or destruction of mastoid air cells. Recent studies have shown that high resolution computed tomography (HRCT) is the best imaging modality for planning therapy by accurately displaying the involvement of the various structures of the middle and inner ear [17].…”
Section: Discussionmentioning
confidence: 99%